Mortaria – with or without stripes - Jauch, Verena (Rei Cretariae Romanae Fautorum Acta, 2022)
For the tri-national research project ‘Limites inter provincias – Rome’s internal frontiers’ the author focused on specific types of mortaria, which are referred to generally as “Raetian” ware. The research showed that the red slipped mortaria were developed in Northern Raetia and are spread widely in the provinces of Germania Superior, Noricum, Pannonia and Britannia. The fact that vessels with early-dating features like handles, horizontal flanges and cut spouts were produced locally in Northern British workshops – probably simultaneous with the Raetian examples – is striking and can only be explained by the military expansion. A group of mortaria with radial striped rims occurs only in the Eastern provinces of Raetia, Noricum and Pannonia. In the more western and northern parts of Germania Superior and Inferior, and northwards to Britain, a different form was developed: the wall-sided mortarium – sometimes decorated with painted stripes on the rim. The distribution of this specific pottery is restricted to Germania Superior and northwards up to Britain. In parts of Southern Germania Superior it seems to follow the course of the Limes towards Raetia.